2013
DOI: 10.1007/s10614-013-9384-9
|View full text |Cite
|
Sign up to set email alerts
|

A Neo-institutionalist Model of the Diffusion of IFRS Accounting Standards

Abstract: International audienceThe purpose of this study is to prepare a diffusion model of the new international accounting standards known as the international financial reporting standards (IFRS). This model fits within the neo-institutional conceptual framework; more specifically, we used the DiMaggio/Powell analytical grid. Our desire to prepare this model was born from the observation that the analytical framework that is generally used to study the adoption of these new standards is the neo-institutional framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
12
0
9
Order By: Relevance
“…They have been identified as one of many international forces behind the process of harmonisation of accounting standards and are the backbone of globalized business. Dufour et al (2014) examined the forces leading an agent (in this case an organisation providing standards for accounting) to adopt, at a given moment, new standards (IFRS). They found that "The two most significant isomorphisms in the simulation are coercive and normative isomorphisms […].…”
Section: Normative Isomorphismmentioning
confidence: 99%
“…They have been identified as one of many international forces behind the process of harmonisation of accounting standards and are the backbone of globalized business. Dufour et al (2014) examined the forces leading an agent (in this case an organisation providing standards for accounting) to adopt, at a given moment, new standards (IFRS). They found that "The two most significant isomorphisms in the simulation are coercive and normative isomorphisms […].…”
Section: Normative Isomorphismmentioning
confidence: 99%
“…The concept which best defines understanding of the process of homogeneous organizational behaviour is isomorphism. This process is characteristic and relevant as an information source to understand the way that organizations share specific equivalent organizational behaviour, although undergoing frequent alterations (Dimaggio & Powell, 1983;Dufour, Teller & Luu, 2014;Smith, Couchman & Beran, 2014). According to Barreto and Baden-Fuller (2006), mimetic isomorphism leads to similar results.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…The concept of institutional isomorphism is a beneficial instrument to cover the policy and the ceremonial peculiarities which intermediate an important element of contemporary organizational life. Therefore, for Dimaggio and Powell (2005), adopting the characteristics of other organizations as an example is the representation of the response to uncertainty (Dufour, Teller & Luu, 2014;Kung, Cegielski, & Kung, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This similarity is a result of a professionally trained workforce who impacts the practices in the companies where they work (Boons & Strannegard, 2000). In fact, normative isomorphism stems from the professional practices of the managers responsible of the companies; managers obtain similar training and transmit the values from this training within companies (Dufour, Teller, & Luu, 2014).…”
Section: Neo-institutional Theorymentioning
confidence: 99%